ANALISIS FUNDAMENTAL MONETER TERHADAP PERUBAHAN KURS RUPIAH SETELAH KRISIS 2008 - Dwita Sakuntala (Jurnal Abdi Ilmu, 2018)
The objectives of this research are to determining the effect of various macroeconomic variables that caused changes in rupiah exchange rate against US dollar and to see the elasticity of the most elastic exchange rate changes. The research model uses multiple linear equations with analysis technique Error Correction Mechanism (ECM) – Domowitz-Elbadawi model. Research period q1.2010 to q4.2016. The empirical results show that partially the change of difference in the money supply, the change of difference in the inflation, the change of difference in the interest rate, the difference in the inflation of the previous period, the difference the interest rate of the previous period, the current account balance of the previous period and error correction variable (EC) of the previous period. While other variables research have no effect. ECM models are valid with error correction coefficients (speed of adjustment) marked positive and statistically significant. R-squared value of 0.837431 means that 83,74% variation in the variable changes in the rupiah exchange rate against the US dollar after the 2008 financial crisis can be explained by the variable changes in the difference in money supply, changes in the difference between real GDP, changes in the difference inflation, changes in the differences interest rate, changes in the current account balance, differences in the previous money supply, previous PDB riil, previous inflation, previous interest rate and previous current account balance.